Validating sweat ammonia as physiological parameter for wearable devices in sports science - Renner, Esther; Lang, Nadine; Langenstein, Bernd; Struck, Matthias; Bertsch, Thomas (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2020)
The measurement of physiological parameters in sweat has long been assumed to offer a non-invasive alternative to conventional blood testing. Recently, advances in sensor technology enable the production of printed sweat sensors applicable for the use in wearable devices. However, the remaining challenge is the determination of the physiological correlation between blood and sweat components. In this study, we conducted ammonia measurements in blood and sweat during a stepwise incremental cycle ergometer test in 40 subjects under completely controlled conditions in a clinical environment to determine the correlation between the ammonium concentrations in blood and sweat. Samples were taken for each workload step separately. Sweat was sampled directly from the upper body, blood was taken from an indwelling cannula at the end of each workload step, respectively. For meaningful classification of the measured quantities, blood lactate and heart rate were monitored additionally. The results for blood ammonium concentration show increasing behavior in good accordance with the established indicators for physical exhaustion, whereas sweat ammonium concentration seems to decrease with workload. This is found to be due to dilution, as sweat rate increases. The presented results provide insight in the correlation between blood and sweat parameters and therefore are of high importance for further development of wearable devices.Clinical Relevance - Sweat sensing opens up new possibilities for non-invasive, continuous in-situ monitoring of physiological parameters for healthcare and sports science applications.
CRIS-Team Scopus Importer:2020-09-25